Cathode Optimization for an Inert-Substrate-Supported Tubular Solid Oxide Fuel Cell - Zhao, Kai; Kim, Bok-Hee; Norton, M. Grant; Ha, Su Y. (Frontiers in Energy Research, 2018)
Inert-substrate-supported tubular solid oxide fuel cells with multi-functional layers were fabricated in this work. The tubular single cells consisted of a porous yttira-stabilized zirconia inert-substrate supporting layer, a Ni anode current collecting layer, a Ni-Ce0.8Sm0.2O1.9 anode electrochemical layer, a yttira-stabilized zirconia/Ce0.8Sm0.2O1.9 bi-layer electrolyte, and a La0.6Sr0.4Co0.2Fe0.8O3-δ cathode. Thickness of the La0.6Sr0.4Co0.2Fe0.8O3-δ cathode layer could be varied from 2.5 to 25.0 μm by controlling the number of dip-coatings in the single cell fabrication process. Electrochemical performance of the tubular single cells was investigated as a function of cathode thickness. Electrode resistance and maximum power density of the single cell were significantly affected by the thickness of the cathode. Increasing the cathode thickness to 15 μm was effective in reducing the sheet resistance of the layer and the electrode resistance of the single cell. Further increasing the cathode thickness induced a higher electrode polarization loss, which originated from insufficient gas diffusion and transport processes. Therefore, the optimum thickness of the La0.6Sr0.4Co0.2Fe0.8O3-δ cathode layer was determined to be 15 μm. At 800 °C, the tubular single cell with the optimum cathode thickness displayed the highest observed maximum power density of 559 mWcm-2 under the hydrogen/air operation mode. Additionally, the tubular single cell exhibited good thermal cycling stability between 800 and 25 °C for five cycles. These results illustrate the advantages of this system for future applications of the inert-substrate-supported tubular single cells in repeated startup and shut down conditions.